2015
DOI: 10.1186/s12905-015-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bone mineral density, its associated physiological factors, and tooth loss in postmenopausal Korean women

Abstract: BackgroundPrevious studies have proposed a relationship between bone mineral density (BMD) and oral health. However, the relationship between BMD and tooth loss in female individuals is not yet well understood. Therefore, the aim of this study was to assess the association between BMD, including its related physiological factors, and tooth loss among postmenopausal women in Korea.MethodsA total of 3,992 postmenopausal women aged 50 years or above were selected from the Fourth and Fifth Korea National Health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
2
18
1
2
Order By: Relevance
“…Great number of recent studies suggests association between low systemic BMD and tooth loss, but still, there is no enough evidence to prove causal relationship. 19,20 In our study, the number of lost teeth was significantly correlated with age and BMD of the hip region but not with the spine region.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Great number of recent studies suggests association between low systemic BMD and tooth loss, but still, there is no enough evidence to prove causal relationship. 19,20 In our study, the number of lost teeth was significantly correlated with age and BMD of the hip region but not with the spine region.…”
Section: Discussioncontrasting
confidence: 47%
“…Often they are unrecognized until advanced stage when complications happen, such as bone fractures and tooth loss. Great number of recent studies suggests association between low systemic BMD and tooth loss, but still, there is no enough evidence to prove causal relationship …”
Section: Discussionmentioning
confidence: 99%
“…First, PMW had a reduced number of teeth, with a high prevalence of NRT < 20 and edentulism. In previous studies, the average NRT for women aged 20 to 64 was 24, only 18.4% had NRT < 20 [17], and the average NRT for PMW was 22–23 [10,14]. The present study indicated that the oral health of these participants was significantly worse.…”
Section: Discussionsupporting
confidence: 38%
“…Studies have indicated that osteoporosis, considered to be a problem of bone destruction and associated with rapid fluctuations in estrogen, exaggerates the loss of alveolar bone, which is involved in the retention of teeth [10,11,12]. In fact, there are many important factors associated with tooth loss and osteoporosis, such as advanced age, poor education [13,14,15], chronic diseases [15,16], tobacco and alcohol use [13,16,17], oral hygiene, and unhealthy diet [16,17,18]. However, there is still controversy in the literature on the relationship between BMD and tooth loss in PMW [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is to say that lower BMD results in more severe periodontal disease (higher CAL and alveolar bone loss) 47 . A 3-year cross-sectional Korean study revealed a strong association between BMD and the number of remaining teeth in postmenopausal women, supporting the relationship between osteoporosis and tooth loss, which is the ultimate result of untreated severe periodontitis 48 . Similarly, Jank KM et al, using data from Korea National Health and Nutrition Examination Survey (KNHANES), demonstrated that normal BMD people had significantly larger number of remaining teeth than those who were diagnosed with osteoporosis or osteopenia, irrespective of their gender 49 .…”
Section: A Bidirectional Association Between Osteoporosis and Chronicmentioning
confidence: 87%